Landing ground reaction forces in figure skaters and non-skaters - Saunders, N. W.; Hanson, N.; Koutakis, P.; Chaudhari, A. M.; Devor, S. T. (Journal of Sports Sciences, 2014)
Researchers and clinicians have suggested that overuse injuries to the lower back and lower extremities of figure skaters may be associated with the repeated high impact forces sustained during jump landings. Our primary aim was to compare the vertical ground reaction forces (GRFs) in freestyle figure skaters (n = 26) and non-skaters (n = 18) for the same barefoot single leg landing on a force plate from a 20 cm platform. Compared with non-skaters, skaters exhibited a significantly greater normalised peak GRF (3.50 ± 0.47 × body weight for skaters vs. 3.13 ± 0.45 × body weight for non-skaters), significantly shorter time to peak GRF (81.21 ± 14.01 ms for skaters vs. 93.81 ± 16.49 ms for non-skaters), and significantly longer time to stabilisation (TTS) of the GRF (2.38 ± 0.07 s for skaters vs. 2.22 ± 0.07 s for non-skaters). Skaters also confined their centre of pressure (CoP) to a significantly smaller mediolateral (M-L) (25%) and anterior-posterior (A-P) (40%) range during the landing phase, with the position of the CoP located in the mid to forefoot region. The narrower and more forward position of the CoP in skaters may at least partially explain the greater peak GRF, shorter time to peak, and longer TTS. Training and/or equipment modification serve as potential targets to decrease peak GRF by distributing it over a longer time period. More comprehensive studies including electromyography and motion capture are needed to fully characterise the unique figure skater landing strategy.